Five Stars: Putting Online Reviews to Work for Your Business - Couzin, Gradiva; Grappone, Jennifer (John Wiley & Sons, Incorporated, 2014)
Create positive visibility for your business with this essential roadmap Everyone now understands the importance of online reviews on sites such as Yelp. This unique book helps you influence the process and leverage the results to increase sales and revenue. Five Stars is the perfect guide to a timely and crucial marketing tactic for today's savvy small business owners and marketers. Find out how to get more (and better) online reviews for your business, track and monitor them, leverage them effectively in social media and elsewhere, and handle negative reviews with aplomb. Packed with tools, techniques, and great case studies, this practical book is what you need to grab the reins, shape the online conversation, and get reviews that sell. Shows you how to get and leverage online reviews from websites such as Yelp and niche sites related to your business Explains tools, techniques, and tactics you can use to start shaping conversations and building positive visibility Demystifies a complex topic, empowering you to make the most of this valuable marketing tactic Written by the expert author team of the popular and practical SEO_An Hour a Day books; the authors offer a similar task-based approach to help you succeed If you're a retail, service, or e-commerce marketer, you won't want to miss Five Stars: Putting Online Reviews to Work for Your Business.